2011
DOI: 10.1007/s00464-011-1835-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding metallic stent as a bridge to surgery versus emergency surgery for obstructive colorectal cancer: a meta-analysis

Abstract: The use of a stent as a bridge to surgery for obstructive left-sided colorectal cancer could increase the chance of primary anastomosis and reduce the need for stoma creation and postprocedural complications. Stent insertion before subsequent surgery has no effect on perioperative mortality and long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(103 citation statements)
references
References 35 publications
9
84
1
7
Order By: Relevance
“…Two recent meta-analyses, although performed very cautiously, confirmed these data and concluded that the insertion of SEMS as BTS appears to be a safe practice, with a low rate of complications and a higher rate of primary anastomosis (21,22 The main drawback of our study is its retrospective nature and the fact that it was not based on intention-to-treat analysis. Several sources of bias could affect our results: first of all, the use of different types of SEMS (WallFlex, Ultraflex, Hanarostent, and Evolution), due to the features of the various materials, their different conformations and their different radial and axial strengths; also, the main parts of the SEMS used were not covered.…”
Section: Discussionsupporting
confidence: 62%
“…Two recent meta-analyses, although performed very cautiously, confirmed these data and concluded that the insertion of SEMS as BTS appears to be a safe practice, with a low rate of complications and a higher rate of primary anastomosis (21,22 The main drawback of our study is its retrospective nature and the fact that it was not based on intention-to-treat analysis. Several sources of bias could affect our results: first of all, the use of different types of SEMS (WallFlex, Ultraflex, Hanarostent, and Evolution), due to the features of the various materials, their different conformations and their different radial and axial strengths; also, the main parts of the SEMS used were not covered.…”
Section: Discussionsupporting
confidence: 62%
“…In our department, the success rate of colonic stent insertion is 92 %, with good short-term and long-term outcomes and low morbidity [15]. According to a meta-analysis of 601 patients in eight comparative studies of SEMS insertion as a BTS in emergency surgery for acute obstructive colon cancer (SEMS group = 232; emergency surgery group = 369), the SEMS group had a shorter intensive care unit stay, a lower stoma creation rate, and a lower rate of postoperative complications (including leakage) [16]. However, there was no significant difference in mortality or long-term outcomes between the two groups [8,17].…”
Section: Discussionmentioning
confidence: 98%
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%